Large‐Area Lasing and Multicolor Perovskite Quantum Dot Patterns. Issue 16 (30th May 2018) - Lin, Chun Hao; Zeng, Qingji; Lafalce, Evan; Yu, Shengtao; Smith, Marcus J.; Yoon, Young Jun; Chang, Yajing; Jiang, Yang; Lin, Zhiqun; Vardeny, Zeev Valy; Tsukruk, Vladimir V.
Abstract: Herein, a novel orthogonal lithography process is reported to pattern all‐inorganic perovskite CsPbX3 (X = Cl, Br, I) quantum dot (QD) arrays which cannot be patterned with traditional approaches. This approach involves a combination of fluorinated polymer and solvent to resolve issues of polar–nonpolar solvent constraints thus enabling the fabrication of complex patterns with high optical gain and multicolor emission. This approach is utilized to fabricate high‐resolution large‐area arrays of microdisk lasers and multicolor (binary and ternary emission) pixels. The optical cavity modes of CsPbBr3 QD microdisk lasers are readily controlled by tuning the disk size, where the mode spacing decreases while the number of modes increases with increasing disk diameter. Finally, the versatility of this approach for the integration of environmentally sensitive QDs with different emission signatures and composition on the same chip, while achieving high‐density, high‐resolution large‐area QD arrays with multicolor pixels, is demonstrated. Abstract : A novel orthogonal lithography process enables the fabrication of large‐area and high‐resolution arrays of various complicated all‐inorganic perovskite quantum dot (QD) patterns with smallest feature size down to several micrometer. Furthermore, QD microdisk lasers with tunable mode number and multicolor QD pixels on the same chip are demonstrated by utilizing this approach.